The Era of Collaborative Management: Navigating the Challenges Faced by Indonesian Local Governments - Denok Kurniasih; Muhamad Yusuf; Anggara Setya Saputra (Jurnal Studi Pemerintahan, 2023)
Lately, there has been a greater recognition of the value of collaboration in government management. It is also recognized that managing collaboration is a complex matter due to the involvement of multiple stakeholders. The goal of this study is to look into the challenges that Indonesian local governments face when implementing a collaborative management scheme. Using a systematic review, we collect evidence from previous studies that analyze local governments that carry out specific collaborative programs. As a result, there are four distinct clusters of challenges, beginning with the complexity of networking, followed by a lack of resources, a lack of interest in collaboration, and political circumstance constraints. From mapping the challenges that are occurring and posing threats to the implementation of this future collaboration, we propose plans that the local government can apply in the future to deal with them. This starts with develop strategic framework, fostering culture of partnership, building capacity-building programs and adopt flexible approach.